Sustainable operation and performance improvement of grid connected DFIG during symmetrical faults using fuzzy controller based enhanced field oriented control. Issue 1 (31st December 2016) - Ananth, D.V.N.; Nagesh Kumar, G.V.
Abstract: According to modern grid regulations, doubly fed induction generator (DFIG) needs to operate without losing synchronism during grid faults. But, severe fault leads to rise in stator and rotor current to a higher value and generator will get damaged. Large oscillations in stator real and reactive power are produced and consequently large torque oscillations get developed. To overcome the above affects due to severe faults, enhanced field oriented control technique (EFOC) is adopted in rotor side control of the DFIG. In EFOC technique, rotor flux reference changes its value from synchronous speed to zero or to a smaller value during fault for injecting current at the rotor slip frequency. In this method, DC-offset component of stator flux is controlled to minimize it. This offset decomposition of flux will be oscillatory in a conventional FOC, whereas in EFOC it can damp quickly. The reference frame for rotor during fault changes with EFOC, so as to make the rotor speed not to deviate much from the reference value. This makes the decomposition of flux during fault to be controlled and make the generator winding current not to exceed to higher values. The proposed EFOC technique with fuzzy controller can damp pulsations in electromagnetic oscillations, improve voltage mitigation and limit surge currents and to have sustained operation of DFIG during voltage sags. The performance of the grid connected DFIG system with voltage sag of 40 and 70% of the rated voltage with symmetrical fault occurring at point of common coupling between 0.1 and 0.3 s are analyzed using simulation studies.